Assessment of burden of drug-resistant tuberculosis at a tertiary care centre in northern India: a prospective single centre cohort study - Richa Misra; Vasudha Kesarwani; Alok Nath (BMJ Open)
Objectives We aim to define the burden of rifampicin monoresistant tuberculosis (TB) at a tertiary care centre in northern India as well as determine the second-line drug susceptibilities (SL-DST) in a subset of patients.Methods A total of 3045 pulmonary (n=1883) and extrapulmonary (n=1162) samples from likely patients with TB were subjected to microscopy, culture and the Xpert MTB/RIF assay from March 2017 to June 2019. SL-DST testing by line probe assay version 2 for fluoroquinolones (FQs) and second-line injectable drugs were performed on 62 samples.Results Out of 3045 samples processed in our laboratory during the study period, 36.1% (1101/3045) were positive for Mycobacterium tuberculosis complex (MTBC) and 21.6% were rifampicin monoresistant (223/1032). The rate of rifampicin resistance in pulmonary samples was 23.5% (166/706) and in extrapulmonary cases, it was 17.4% (57/326). Out of 62 cases included for second-line testing, 48 were resistant to FQs (77.4%) while 11 were extensively drug resistant.Conclusions India urgently needs to arrest an emerging multidrug-resistant TB epidemic with associated resistance to FQs. A robust surveillance system is needed to execute the National Strategic Plan for 2017–2025.